The Sami People in Scandinavia: Government Policies for Indigenous Language Recognition and Support in the Formal Education System - O'Dowd, Mina (Springer, 2015)
The Sámi people in Scandinavia have experienced a long history of discrimination, oppression, neglect, ridicule, and theft. Some scholars compare the history of the Sámi with that of the American Indian population. Today the Sámi who live in Sweden, Norway and Finland, together with the Sámi in Russia have managed to improve their situation through concerted efforts, collaboration with one another, and cooperation with the international movement for the rights of indigenous peoples. More recently, the Sami have received support from both the European Union and the United Nations. Despite international support, the right of the Sámi people for self-determination has not been acknowledged by the Swedish, Norwegian or Finnish governments. The Sami’s right to instruction and education in their own mother tongue has not been adequately addressed. Rather government policies in the Scandinavian countries can at best be described as policies for language maintenance, while what is sorely needed are policies that re-vitalize language use among all Sámi and provide support for endangered or nearly-extinct Sámi languages. Much remains to be done for this indigenous people, not the least of which is acknowledgement of right to their land, their hunting and fishing rights and their right to determine if and how their land is to be exploited.